Barriers to Colorectal Cancer Screening in Pakistan - Hasan, Fariha (Cureus, 2017)
Background The prevalence of colorectal cancer (CRC) is growing in Pakistan; however, there are no national screening programs or guidelines in place to curb its development. This study was conducted with the aim of ascertaining public awareness and attitudes regarding CRC and current screening practices. Furthermore, the study assessed perceived barriers which could impact future screening processes. Methods A cross-sectional, questionnaire-based study was conducted among urban dwellers of Karachi, Pakistan. We excluded any individuals belonging to the medical profession, those diagnosed previously with CRC or having any significant co-morbidity. The validated and pre-tested questionnaire was administered among the study participants to record demographic information, awareness of CRC risk factors, symptoms and screening tests. Attitudes towards screening and perceived barriers to screening were also assessed. Data were analyzed using Statistical Package for Social Sciences (SPSS version 20.0) (IBM Corp., Armonk, NY). A knowledge score, out of a total of 14 points was calculated to reflect a participant’s overall knowledge regarding CRC risk factors and signs/symptoms. Results The prevalence of CRC screening in eligible individuals (50 years or older) was 2.6% in our study population. Positive attitudes towards CRC management and screening were observed, with 75.1% (n = 296) acknowledging the preventive role of screening tests. Despite this only 14.9% (n = 58) of study participants expressed a future desire to undergo screening. Major barriers to screening were reported to be “a lack of knowledge regarding the screening procedure”, a “lack of screening facilities” and that the “screening procedure is too expensive”. A majority (n = 285, 72.3%) of the participants expressed a greater willingness to undergo screening if their doctor recommended it. Conclusion A national CRC screening and awareness program should be launched to promote awareness and facilitate screening in risk groups. General practitioners are needed to play a key role in counseling patients and endorsing healthy screening practices.